The Implementation of Human Organ Monopoly Media to Improve Science and Social Studies (IPAS) Learning Outcomes of Fifth-Grade Students at MI At-Taufiq Samarinda Ulu - Ikrima Salsabila; Husnul Khatimah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the application of Human Organ Monopoly media in improving the learning outcomes of fifth grade students of MI At-Taufiq Samarinda Ulu. The background of this study is the low learning outcomes of students on the material of human organs, where out of 25 students there are 10 students who have not reached the Learning Objective Achievement Criteria (KKTP). The approach used is Classroom Action Research (CAR) with the application of educational game-based media monopoly. The results of the literature review and previous research indicate that the use of Monopoly media can significantly increase student engagement, motivation, and learning outcomes. Thus, the Human Organ Monopoly media is believed to be an innovative solution to overcome the problems of learning science at MI At-Taufiq Samarinda Ulu.